2001
DOI: 10.1034/j.1600-0587.2001.240102.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental perturbations on abundance of subarctic plants after three, seven and ten years of treatments

Abstract: Analyses of changes in vegetation were carried out after three, seven and ten years of fertilizer addition, warming and light attenuation in two subarctic, alpine dwarf shrub heaths. One site was just above the tree line, at ca 450 m a.s.l., and the other at a much colder fell‐field at ca 1150 m altitude. The aim was to investigate how the treatments affected the abundance of different species and growth forms over time, including examinations of transient changes. Grasses, which increased in abundance by fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 33 publications
10
101
1
Order By: Relevance
“…Plants invest part of their additional production in a higher leaf area and in horizontal and vertical canopy growth, increasing light interception and further augmenting production. The simulated productivity increase is consistent with results from tundra warming experiments (Michelsen et al 1996;Arft et al 1999;Graglia et al 2001;Walker et al 2006;Olsrud et al 2010), and productivity trends inferred from satellites (Bunn and Goetz 2006;Beck and Goetz 2011), while the increase in LAI is consistent with a positive trend in remotely sensed NDVI across the Arctic tundra biome over the same period ( Fig. 3; Bhatt et al 2010).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Plants invest part of their additional production in a higher leaf area and in horizontal and vertical canopy growth, increasing light interception and further augmenting production. The simulated productivity increase is consistent with results from tundra warming experiments (Michelsen et al 1996;Arft et al 1999;Graglia et al 2001;Walker et al 2006;Olsrud et al 2010), and productivity trends inferred from satellites (Bunn and Goetz 2006;Beck and Goetz 2011), while the increase in LAI is consistent with a positive trend in remotely sensed NDVI across the Arctic tundra biome over the same period ( Fig. 3; Bhatt et al 2010).…”
Section: Discussionsupporting
confidence: 84%
“…Despite numerous local exceptions, the weight of evidence from observational studies suggests that, in general, Arctic vegetation is responding to rising temperatures through increases in productivity, density, cover and stature of vegetation and, in many areas, an increase in woody biomass and the representation of trees and shrubs (Post et al 2009;Callaghan et al 2011;Elmendorf et al 2012). These findings are qualitatively consistent with expectations based on the results of tundra warming experiments (Chapin et al 1995;Michelsen et al 1996;Arft et al 1999;Graglia et al 2001;Walker et al 2006;Olsrud et al 2010), and simulations using vegetation models (Kaplan et al 2003;Smith et al 2008a;Wolf et al 2008a;Wramneby et al 2010).…”
Section: Introductionsupporting
confidence: 72%
“…The experiments in the forest understory (Press et al 1998), the wet (Sorensen and Michelsen 2011) and the mesic (Graglia et al 2001) heaths and the high altitude fellfield have shown that both warming and, in particular, enhanced nutrient availability promote a higher biomass of dwarf shrubs, but that subcanopy mosses and lichens decline strongly as the plant canopy closes. Hence, plant species diversity is expected to be reduced in subarctic heaths following warming because of loss of cryptogams, while plant C accumulation is expected to increase as woody plants with large stem masses increase their cover.…”
Section: Plant Functional Types Nutrient Availability and Responsivmentioning
confidence: 99%
“…In a tundra ecosystem in Northern Sweden, Graglia et al (2001) showed in a 10-year fertilization experiment that grasses increased in abundance in response to fertilizer application. Similarly, Van Wijk et al (2003) reported that the biomass of deciduous shrub and graminoid plant types responded most strongly to nutrient addition on sites in Alaska and Northern Sweden during a long-term fertilization experiment ([3 year).…”
Section: Graminoidsmentioning
confidence: 99%
“…In environments with sufficient nutrients, plants with a high potential growth rate and a high leaf area ratio (the leaf area per unit total plant biomass) will have advantages over plants with lower potential growth rate (Berendse 1994;Lambers et al 1998). This might explain why graminoids often increase in abundance after the application of fertilizer (Graglia et al 2001;Van Wijk et al 2003;Bret-Harte et al 2004. In bog ecosystems, a shift in dominance from one plant functional group toward another might have great impact.…”
Section: Introductionmentioning
confidence: 99%